Methicillin resistant stahphylococcus aureus (MRSA) septicemia in pemphigus foliaceus - A coalition partners in resistant cases - Jindal, Anuradha; Rao, Dr. Raghavendra (Journal of Pakistan Association of Dermatologists, 2019)
Infection contributes to considerable morbidity and mortality in patients with autoimmune bullous disorders (AIBDs) such as pemphigus. Increased susceptibility to infection in this population may occur via 3 primary mechanisms- defective barrier function as a result of blistering and subsequent erosions, down regulation of immunity due to medications used in the treatment of AIBDs and finally, immune dysregulation associated with autoimmunity.1 In pemphigus, sepsis is the most common cause of death, with staphylococcus aureus being the most frequently implicated organism.2 We hereby report two cases of methicillin resistant staphylococcus aureus (MRSA) septicemia in pemphigus foliaceus (PF) patients rendering them resistant to conventional immunosuppressive therapies. Â